Manfaat Air Bagi Tumbuhan: Perspektif Al-Qur’an dan Sains - Suskha, Ahlam; AM, Rusydi; Wusqa, Urwatul (AL QUDS : Jurnal Studi Alquran dan Hadis, 2020)
The Benefits of Water for Plants: the Perspectives of Al-Qurâ€™an and Science Water is the main element of life. The existence of water is fundamentally vital for creatures on earth, especially for plants which require water to grow. In the Qurâ€™an, many verses discuss water, such as ethical principles with respect to the importance of water and its benefits for life. This study aimed to discuss the benefits of water for living things, especially plants based on the Qurâ€™anic guidance and further compared with scientific theories. This study used the thematic interpretation method (mawdhu’i) with the thematic term model. The focus of this studywas the Qurâ€™anic verses related to water, especially the word water associated with plants. This study showed that the word water (Ø§Ù„Ù…Ø§Ø¡) is repeated 63 times in 41 surahs of the Qurâ€™an, with someassociated words, namely anzala (lowering), sabba (pouring out), asqa (watering / giving drink), ahya (reviving) and akhraja (spawning). The benefits of water for plants according to the Qur’an are ahya (reviving), as found in the QS. Al-An’am: 99. According to science, there are many functions of water for plants such as the main constituent of protoplasm and being a solvent for nutrients needed by plants